2016
DOI: 10.1126/science.aaf2349
|View full text |Cite
|
Sign up to set email alerts
|

Slow slip near the trench at the Hikurangi subduction zone, New Zealand

Abstract: The range of fault slip behaviors near the trench at subduction plate boundaries is critical to know, as this is where the world's largest, most damaging tsunamis are generated. Our knowledge of these behaviors has remained largely incomplete, partially due to the challenging nature of crustal deformation measurements at offshore plate boundaries. Here we present detailed seafloor deformation observations made during an offshore slow-slip event (SSE) in September and October 2014, using a network of absolute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
512
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(532 citation statements)
references
References 43 publications
19
512
1
Order By: Relevance
“…SSE slip near Gisborne predominantly occurs beneath the offshore region, with the downdip limit of slip near the coastline, and the SSEs appear to rupture similar areas of the interface repeatedly . A recent seafloor geodetic experiment has shown that slow slip occurs to within at least 2 km of the seafloor beneath the Expedition 375 drilling transect, and it is possible that slow slip continues all the way to the trench (Wallace et al, 2016).…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…SSE slip near Gisborne predominantly occurs beneath the offshore region, with the downdip limit of slip near the coastline, and the SSEs appear to rupture similar areas of the interface repeatedly . A recent seafloor geodetic experiment has shown that slow slip occurs to within at least 2 km of the seafloor beneath the Expedition 375 drilling transect, and it is possible that slow slip continues all the way to the trench (Wallace et al, 2016).…”
Section: Geological Settingmentioning
confidence: 99%
“…These rocks comprise the protolith and reveal the initial conditions for fault rocks that are transported into the SSE source zone at greater depth. In the case of the shallow fault zone, these materials may in fact host SSEs if the events propagate to the trench (e.g., Wallace et al, 2016 To achieve this goal, characterization of the incoming stratigraphy and upper oceanic basement rocks, together with the shallow, most active strand of the frontal thrust system, is essential. This characterization involves a combination of coring, downhole measurements, and logging at proposed Sites HSM-13B, HSM-08A, and HSM-18A, followed by a strategy of carefully coordinated sampling and postexpedition laboratory analyses (e.g., Screaton et al, 2009;Underwood et al, 2010).…”
Section: Scientific Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…SSEs occur near Gisborne beneath the offshore region, with the downdip limit of slip near the coastline and repeated SSE rupture of the same areas of the interface . A recent seafloor geodetic experiment has shown that slow slip occurs to within 2 km of the seafloor beneath the outer part of the proposed drilling transect, and possibly continues all the way to the trench ( Figure F4) (Wallace et al, 2016).…”
Section: Slow Slip Events On the Hikurangi Subduction Marginmentioning
confidence: 99%
“…, even though some happen at shallow depth, notably in New Zealand [4][5][6] and Costa Rica 7,8 . Slow-slip events at subduction zones worldwide often embody similar, characteristic features [9][10][11][12][13] .…”
mentioning
confidence: 99%